Penerapan Media Audio Visual Dalam Cerita Legenda Danau Kelimutu Untuk Meningkatkan Kemampuan Menyimak Siswa Kelas VB SDI Bhonawa I Ende - Fransiska M. Loni (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
This study aims: (a). To find out the design of Indonesian language learning using audio-visual media for grade VB students of SDI Bhonawa 1 Ende. (b). This is to determine the application of audio visual media in language learning for grade VB students at SDI Bhonawa 1 Ende. This research was conducted using a classroom action research method (PTK) which consists of two cycles. Each cycle consists of four stages, namely; observation, planning, action, and reflection. Data collection techniques used in this study were tests, observation, interviews, and documentation. The collected data were analyzed descriptively qualitatively and descriptively quantitatively. From the results of the study showed that the use of audio-visual media in Indonesian Language subjects concluded that the students' abilities in the learning process had increased from each cycle. The learning outcomes in the first cycle with an average value of 47% and meant that the criteria were quite good and there was an increase in the second cycle, the learning ability increased by an average of 100%.